ISLAMIC PERSPECTIVE AT THE CONSUMPTION ETHICS OF STUDENTS IN AN-NIDA SALATIGA ISLAMIC BOARDING IN THE COVID-19 PANDEMIC - Choirul Amirudin; Ahmad Fikri Sabiq (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2022)
This study aims to determine the ethical patten of consumption of the Islamic students at  An-Nida Islamic boarding school. The research was conducted in November 2020 using google form and other reputable journals with the keyword "Islamic Comsuption Ethics". Based on the results of the analysis, it can be concluded that the consumption behavior of the student at the An-Nida Salatiga Islamic Boarding School has followed the procedure with consumption ethics regulated in Islam. This can be seen from the exposure of the study that the comsumption pattern of the An-Nida Islamic Boarding School students during the pandemic and normal times is not much different. Even during the pandemic, the consumption patterns of the An-Nida students were more regular.